THE IMPACT OF CUSTOMER EXPERIENCE, SALES PROMOTION, SERVICE QUALITY, AND PRODUCT AVAILABILITY ON CUSTOMER LOYALTY IN TOKOPEDIA’S RETAIL BUSINESS: THE MEDIATING ROLE OF CUSTOMER SATISFACTION - Dr. Edy Sulistiyawan, M.Si.; M. Adhi Prasnowo; Mustafa Hermanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2026)
This study investigates the determinants of e-loyalty among Tokopedia users by applying the Stimulus–Organism–Response (S-O-R) model. The model conceptualizes Customer Experience (CX), Promotion, E-Service Quality, and Product Availability as external stimuli (S) that influence E-Loyalty (R) both directly and indirectly through E-Satisfaction (O). Data were collected from 150 active university students in Surabaya who had made purchases on Tokopedia within the past six months. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the measurement and structural models. Results indicate that all stimulus variables significantly affect both e-satisfaction and e-loyalty. Among them, Product Availability shows the strongest direct effect on e-loyalty, while Promotion has the largest impact on e-satisfaction. Moreover, e-satisfaction serves as a significant mediator between all stimulus variables and e-loyalty, confirming the central role of emotional and cognitive satisfaction in shaping long-term customer commitment. The model explains 59.8% of the variance in e-loyalty and 44% in e-satisfaction, demonstrating robust explanatory power. These findings emphasize that enhancing customer experience, service quality, promotional relevance, and product reliability are crucial strategies for fostering sustained e-loyalty in competitive e-commerce platforms.